Comparison of the prognosis and lymph node metastasis between no tumor budding and low-grade tumor budding in T1 and T2 colorectal cancer - Jong Yoon Lee; Mee Sook Roh; Jong Hoon Lee; Seun Ja Park; Hee Kyung Chang; Seok Won Jung; Ji Hye Kim; Busan Ulsan Gyeongnam Intestinal Study Group Society (BIGS) (Scientific Reports)
Abstract Tumor budding is a significant prognostic factor in colorectal cancer (CRC) management and is graded as follows: 0–4 buds as low, 5–9 buds as intermediate, and > 10 buds as high. However, the specific prognostic difference between cases with 0 buds (BD0) and those with 1–4 buds (BD1) is not well established owing to a lack of comparative studies. This study aimed to examine and compare the rate of lymph node (LN) metastasis and prognosis by distinguishing between BD0 and BD1 within the low-grade category (0–4 buds) of tumor budding in submucosa (T1) and muscularis propria (T2) CRC. We retrospectively identified 223 cases of T1 and T2 CRC underwent surgery from 2015 to 2018 across three medical institutions using medical records. Pathology, including assessing tumor budding, was subsequently reconfirmed, and the recurrence and survival of patients were evaluated up to December 2023. Patients in the BD1 group exhibited a higher T stage than those in the BD0 group, accompanied by significantly increased rates of lymphovascular and perineural invasion. The prevalence of LN metastasis was 14.8%. No significant differences in LN metastasis were observed between the BD0 and BD1 groups. In a multivariate analysis exploring factors associated with LN metastasis, relevant factors included lymphatic invasion, perineural invasion, and ≥ 5 buds. There were no significant differences in 5-year survival and progression free survival rates between the BD0 and BD1 groups (P = 0.971). This study confirmed that there was no significant difference in LN metastasis or prognosis between patients with BD0 and BD1.